Photon Bubbles in the Circumstellar Envelopes of Young Massive Stars - Turner, N. J; Quataert, E; Yorke, H. W (The Astrophysical journal, 2007)
We show that the optically thick dusty envelopes surrounding young high-mass stars are subject to the photon bubble instability. The infrared radiation passing through the envelope amplifies magnetosonic disturbances, with growth rates in our local numerical radiation MHD calculations that are consistent with a linear analysis. Modes with wavelengths comparable to the gas pressure scale height grow by more than 2 orders of magnitude in 1000 yr, reaching nonlinear amplitudes within the envelope lifetime. If the magnetic pressure in the envelope exceeds the gas pressure, the instability develops into trains of propagating shacks. Radiation escapes readily through the low-density material between the shocks, enabling accretion to continue despite the Eddington limit imposed by the dust opacity. The supersonic motions arising from the photon bubble instability can help explain the large velocity dispersions of hot molecular cores, while conditions in the shocked gas are suitable for maser emission. We conclude that the photon bubble instability may play a key role in the formation of massive stars.